REVISION USING EXPLANATION AND RECALL (E&R ) AT KOLEJ MARA BANTING - Awang, Satinah; Binti Hj Iksan, Zanaton (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract The objective of this research is to increase the level of International Baccalaureate (IB) student achievement at Kolej MARA Bantingby using Explanation and Recall Revision Tools. This was done by identifying the level of studentâs confident toward the IB Examination after went through two months programme in the Explanation and Recall technique. In this research the reflection ofIB 2015 Candidates toward E & R Program are analyzed based on self-administered questionnaire that have been written by them. The purposive respondents for this action research are Engineering and Medic IB 2015 Candidates. The overall findings are summarized based on reflection from Candidates of International Baccalaureate Diploma programme (IBDP) 2015. Based on the findings, E & R are a good technique in order to prepare IB Examination 2015 Candidates in term of confident level. From the finding also, majority of the candidates agree E & R Revision Tool is effective provided that the student do the revision before the explanation and recall. Based on the reflection given in the research, 2 themes have been identify which are confident level and effectiveness. A further investigation need to be carried out in order to identify others factor that contribute to the IBDP Candidates achievement. Analysis performance of the student also suggested to be analyze upon receive of the IBDP results.Key words : E & R, Effectiveness and Confident.